Authorization, rationalization, and moral evaluation: legitimizing acupuncture in Hong Kong's newspapers. Issue 2 (3rd March 2016) - Dong, Dong; Chan, Kara
ABSTRACT: Hong Kong has always been regarded as a critical region of Cultural China. Surprisingly, traditional Chinese medicine has not yet been accepted as legitimate in the city. This study uses acupuncture as a case to investigate the way media texts work to organize a field of knowledge and practices about health in a post-colonial society where contrasting perspectives and hybrid ideas rooted from the East and the West intermingle. Acupuncture is conceptualized as socially constructed health knowledge that has become increasingly legitimate in media discourse. Through a mixed-method approach that combines discourse and content analysis, a total of 666 news articles related to acupuncture published in two Hong Kong newspapers over a 10-year period were analyzed. Three major forms of discursive construction of legitimation – authorization, rationalization, and moral evaluation – were identified and elaborated in association with the texts and the social contexts. This study reveals a complex process of generating legitimacy for health knowledge through news narratives.